Tactile Score A Knowledge Media for Tactile Sense - Suzuki, Yasuhiro; Suzuki, Rieko; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2014)
This book deals with one of the most novel advances in natural computing, namely, in the field of tactile sense analysis. Massage, which provides relaxation and stimulation for human beings, is analyzed in this book for the first time by encoding the motions and tactile senses involved. The target audience is not limited to researchers who are interested in natural computing but also includes those working in ergonomic design, biomedical engineering, Kansei engineering, and cognitive science.
Introduction -- Tactile Workshop -- Experiments relating to Massage -- Tactile Score, (3z(BSyoku-fu$1!"(3y (B-- Investigation of massage by using Tactile Score -- Method of Composing Massage -- Future Tactile sense.s
Keywords: Engineering; Computer simulation; Computer science; Engineering design; Biomedical engineering; Engineering; Computational Intelligence; Simulation and Modeling; Biomedical Engineering; Computational Science and Engineering; Engineering Design